Natural bio-antimutagenic activity of rooibos tea (Aspalathus linearis) as expressed by the Ames, Toxi-Chromo and SOS-Chromo tests - Standley, Lauren (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. in Food Science) -- University of Stellenbosch, 1999.